2020
DOI: 10.1101/2020.03.16.20036806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of evidence during disease outbreaks: lessons learnt from the Zika virus outbreak

Abstract: Introduction: Outbreaks of infectious diseases trigger an increase in scientific research and output. Early in outbreaks, evidence is scarce, but it accumulates rapidly. We are continuously facing new disease outbreaks, including the new coronavirus (SARS-nCoV-2) in December 2019.The objective of this study was to describe the accumulation of evidence during the 2013-2016 Zika virus (ZIKV) outbreak in the Pacific and the Americas related to aetiological causal questions about congenital abnormalities and Guill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Analysis of published studies showed that estimates of the duration of infection decreased over time as less biased studies were published. 56 Transmission from pre-symptomatic individuals has been found to occur one to three days before symptom onset. 57 The degree of transmissibility of asymptomatic infection is not known, but it has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of published studies showed that estimates of the duration of infection decreased over time as less biased studies were published. 56 Transmission from pre-symptomatic individuals has been found to occur one to three days before symptom onset. 57 The degree of transmissibility of asymptomatic infection is not known, but it has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 346 publications about Zika virus, we described the temporal sequence of publication of types of study to investigate causality. 9 Others have assessed the accumulation of study designs over time during the SARS-CoV-2 outbreak and concluded that early in the outbreak, simple observational studies and narrative reviews were most abundant. 10 Here, we proposed a hypothetical sequence: first, anecdotal observations are reported in case reports or case series.…”
Section: Introductionmentioning
confidence: 99%